SHORT-RUN AND LONG-RUN RELATIONSHIP OF ISLAMIC HOME FINANCING IN MALAYSIA: ANALYSIS ON ISLAMIC BANKS - Siti Maryam Idris; Zakaria Bahari; Fadzila Azni Ahmad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
Islamic home financing is a service offered by Islamic banks according to the Islamic principle. In Malaysia, it has been offered since the early 1980s. The demand for Islamic home financing in Malaysia has increased over time. Therefore, this study would like to delve into the short-run and long-run relationship between the factors involved in Islamic home financing. Past studies highlighted the microeconomic factors and macroeconomic factors in Islamic banks that contribute to the growth of Islamic home financing in Malaysia. Thus, this study would include four factors comprised of deposits, liabilities, GDP, and government expenditure. Deposits and liabilities are categorized into microeconomic factors, whereas GDP and government expenditure are macroeconomic factors. The first objective is to identify the short-run and long-run relationship between the factors mentioned above on Islamic home financing in Malaysia. The second objective is to analyze the causality effects of the factors on Islamic home financing in Malaysia. The methodology comprises of quantitative research design. Data collection is based on secondary data collection, which was retrieved through documentation review and statistical highlights from Bank Negara Malaysia. The data comprise the first quarter of 2010 until the second quarter of 2021. Analysis data is conducted through an econometric approach within time series data which is the ARDL test and Granger causality test. The findings of this study would emphasize the importance of microeconomic factors and macroeconomic factors on Islamic home financing. It would encourage the supply and growth of Islamic home financing by Islamic banks in Malaysia in the future.